Tribological behavior of dual and triple particle size SiC reinforced Al0MMCs: a comparative study - Maleque, Md. Abdul; Karim, Md Rezaul (Emerald Group Publishing Limited, 2008)
Purpose- The aim is to study the tribological behavior of dual particle size (DPS)and triple particle size (TPS) SiC reinforced aluminium allloy based metal matrix composites - MMCs (Al/SiCp MMC)SiCp/Al-MMC). Design /methodology /approach- Al-MMCs were prepared using 20 vol% SiC reinforcement into aluminum metal matrix and developed using a stir casting process. Stir casting is a primary process of composite production whereby the reinforcement ingredient material is incorporated into the molten metal by stirring. The triple particle size (TPS) composite consist of SiC of three different sizes viz., coarse, intermediate and fine. The solution heat treatment was done on as cast (AC) composite at 540 0C for four hours followed by precipitation treatment. The wear test was carried out using a pin-on-disc type tribo-test machine under dry sliding condition. A mathematical analysis was also done for power factor values based on wear and friction results. The wear morphology of the damaged surface was also studied using optical microscope and scanning electron microscope (SEM) in this investigation. Findings- The test results showed that heat treated composite exhibited better wear resistance properties compared to as cast composite. It is anticipated that heat treatment could be an effective method of optimizing the wear resistance properties of the developed Al-MMC material.